Implementasi Data Mining Untuk Klasifikasi Stuting Gizi Pada Balita di Surabaya Menggunakan Metode K-Medoids - Wahyudi, wiwid; Alvina Chintya Putri Herlena; IrdhaYunianto (Jurnal Publikasi Teknik Informatika, 2023)
With the development of the times, it is undeniable that science and technology as well as the ease of internet development make it easier for people to identify good nutrition that is needed by the body.humans, especially in toddlers who are in the processdevelopment is veryfast. Growth monitoring in toddlers is very important. To determine quality life, Psychic and the future of toddlers.Process monitoring can done in a cooperative way between parents and government, especially midwives and Posyandu cadres routine every period. Growing up and developing toddlers can seen with the indicators BB/TB, TB/U, BB/U, then stored in the Towards Healthy Card (KMS) data as picture on parents to really pay attention her toddler. This is for monitoring purposes growth and development of toddlers every month. In cases of stunting Nutrition in toddlers Clustering process using the Kmedoids method has low accuracy so it is not precise if used. It will be more effective when using the method Another clustering so that the accuracy value is obtained higher in order to facilitate the performance of midwives or cadres Posyandu is in the process of grouping toddler data who experienced good nutrition, moderate nutrition, malnutrition and malnutrition bad.